Spatial Analysis of Tourism Objects and Facilities in Simarjarunjung Natural Tourism Area, North Sumatra Province, Indonesia - Ambarita, Rolasdo; Agus Purwoko; Thoha, Achmad Siddik (Journal of Sylva Indonesiana, 2023)
North Sumatra is one of the provinces in Indonesia that has a wealth of natural resources in the form of natural beauty.Â  One place whose potential natural beauty stands out is the Simarjarunjung area, which is on the north side of Lake Toba. The purpose of this study was to analyze the spatial distribution of tourist objects, natural tourism amenities, and infrastructure in the Simarjarunjung nature tourism area. This research method uses spatial analysis. There are 11 tourist attractions located in the Simarjarunjung natural tourism area that have the potential to be utilized by the manager for natural tourism activities. My Maps technology from Google is used to facilitate access to information so that it is expected to have a positive impact. One of them is the promotion of tourist attractions so that they can be easily accessed by anyone through online networks. The availability of data on the distribution of tourist attractions, attractions and facilities / infrastructure resulting from this research is expected to be a means to be able to increase visitor access to find out information about tourism contained in Simarjarunjung tourist attractions. Each tourist attraction in the Simarjarunjung area has various attractions and tourist facilities, each of which is the attraction and uniqueness of each tourist attraction